The Extraglycemic Effect of SGLT-2is on Mineral and Bone Metabolism and Bone Fracture - Dong, Bingzi; Lv, Ruolin; Wang, Jun; Che, Lin; Wang, Zhongchao; Huai, Zhouyang; Wang, Yangang; Xu, Lili (Frontiers in Endocrinology, 2022)
Type 2 diabetes mellitus (T2DM) is a risk factor of osteoporosis. The effects of T2DM and anti-diabetic agents on bone and mineral metabolism come into notice. Sodium-glucose co-transporter 2 inhibitors (SGLT-2is) promote urinary glucose excretion, reduce blood glucose level, and improve cardiovascular and diabetic nephropathy outcomes. In this review, we focused on the extraglycemic effect and physiological regulation of SGLT-2is on bone and mineral metabolism. SGLT-2is affect bone turnover, microarchitecture and bone strength indirectly. Clinical evidence of meta-analysis show SGLT-2is may not increase the bone fracture risk. The effect of SGLT-2is on bone fracture is controversial, further investigation from real-world study is needed. Based on its significant benefit of cardiovascular and chronic kidney disease (CKD) outcomes, SGLT-2is are outstanding choice. Bone mineral density (BMD) and fracture risk evaluation should be considered for patients with high risk of bone fracture.